Social Construction of Demangan Tomb Pilgrims at Blitar - Syaikhu Maqronodin Shomad; Ahmad Nurcholis (Transformatif, 2022)
The purpose of this study is to describe the social construction of the Dermojayan village community towards the Demangan tomb pilgrimage phenomenon which then becomes an understanding, perception, and religious emotion to form a predisposition in carrying out their religious traditions. In order to obtain accurate data, this research uses a descriptive qualitative case study using a phenomenological approach. The grand theory in this study adheres to the theory of social construction analysis from Peter L Berger and Thomas Luckman (1967) which says that individual knowledge forms predispositions as part of social action. The results of this study indicate that the social construction that grows on the perpetrators of the Demangan tomb pilgrimage arises because of the values inherited by their ancestors. The community carries out tomb pilgrimages with the aim of conveying gratitude to their ancestors, expressing respect for their ancestors, offering prayers to obtain blessings, and as an embodiment of preserving the relics of the ancestors of the Dermojayan village. The social values contained in the phenomenon of the Demojayan village tomb pilgrims are manifested in a series of processions and offerings at the time of the tomb pilgrimage as a manifestation of social life inherited by the village ancestors